Performance of Hydro-Primed Brassica napus L. Seeds Under Different Saline Regimes, A Preliminary Approach: Performance of Brassica napus L. Seeds Germination (Biological Sciences - PJSIR, 2023)
In the present study effect of hydro-priming on some primary parameters (germination, radicle/plumule length and biomass) of canola seed was investigated that were subjected to various saline doses. The experiment was based on 3 factorial complete randomized design with salinity levels (0, 20 mM, 30 mM, 40 mM and 50 mM) as a first factor, priming (non-primed and hydro-primed) levels as second factor and canola cultivars (Abasin-95, Dur e Nifa and Nifa Gold) as third factor. Results confirmed significant (Alpha = 5 % probability level) effects of salinity on radicle/plumule growth and fresh biomass of Brassica napus L, whereas data related to germination displayed non-significant variations (Alpha =  5 % probability level). Subsequently, studied parameters recorded significant variations for priming levels and canola cultivars. In the same way, first order interaction (salinity doses x priming levels) induced significant effects on plumule size and fresh weight of Brassica napus L. in contrast to other parameters (radicle growth and germination). The 2nd order interaction (priming levels x cultivars) was proved to cause highly significant effects on all the selected parameters of Brassica napus L. In case of 3rd order interaction (salinity doses x cultivars) the response of Brassica napus L. was significant for plumule and radicle growth only. Consequently, the 4th order interaction (salanity doses x priming levels x cultivars), instigated non-significant effects on all the studied parameters of Brassica napus L. except radicle growth. The increase in seedling growth and fresh weight of Brassica napus under most of salinity doses confirmed canola as a salt tolerant plant as shown by previous studies. Furthermore, present study justified better performance of non-primed seeds over hydro-primed canola seeds. Among the tested canola cultivars, Nifa Gold proved to be more adapted to salinity than other cultivars and is advisable for growing on saline land in Pakistan.